PENGARUH JIGSAW BERBANTUAN MEDIA GAMBAR TERHADAP HASIL BELAJAR IPA KELAS V DI SD GUGUS V - Luh Juli Utariasih (Indonesian Journal Of Educational Research and Review, 2018)
This study was aimed to know the differentciateof the result study at sains between group of stundents who followed the study with cooperative jigsaw type that combined by picture media and the students who did not used cooperative jigsaw type combined by picture media. This study was belong to quasi exsperiment with Nonequivalent Post-Test Only Control Group Design. The population of this study was all of the five grade student at five troop in Banjar subdistrict. The teknic model defermined by used random sampling. The method  to collected date of resuit study used multipie choice method. The date collected analysis by statistic descriptive and statistic inferensial t-experimen technic with formulas polled varians.the result of the study showed that there are significance differlance on the sains result study between the group of students who was followed study with cooperative jigsaw type that combinated by picture  media and group of students who did not used study model cooperative jigsaw type that combined by picture on five grade students at troop in banjar subdistrict. That all showed by the hipotesis analysis result with t-experimen  t  (3,292732) > t  (2,022). Next the mean of experiment group was (20,64)the result was high more that mean of control group (18,2).it’s mean that the study that used study model cooperative jigsaw type combined by picture gave effect of sains study result gave grade student at five troop in Banjar subdistrict in the academic year 2017/2018.